2013
DOI: 10.1186/1475-2891-12-158
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic signature associated with the Western dietary pattern: a cross-sectional study

Abstract: BackgroundMetabolic profiles have been shown to be associated to obesity status and insulin sensitivity. Dietary intakes influence metabolic pathways and therefore, different dietary patterns may relate to modifications in metabolic signatures. The objective was to verify associations between dietary patterns and metabolic profiles composed of amino acids (AAs) and acylcarnitines (ACs).Methods210 participants were recruited in the greater Quebec City area between September 2009 and December 2011. Dietary patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
60
0
11

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 32 publications
7
60
0
11
Order By: Relevance
“…Furthermore, the impact of the HSu diet on leptin serum levels and on leptin receptor expression would be of interest. Overall, our study shows that nine week of HSu-diet, which mimics at least in part Western diets [10,11,47], can lead to impaired hepatic glucose and lipid metabolism, typical features of T2DM, already present in this prediabetic model, even in the absence of obesity. This animal model of diet-induced prediabetes shows reduced glucose tolerance, postprandial hyperglycemia, hyperinsulinemia, reduced insulin sensitivity (resistance), and hypertriglyceridemia, together with impaired gluconeogenesis and lipogenesis ( Figure 8).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the impact of the HSu diet on leptin serum levels and on leptin receptor expression would be of interest. Overall, our study shows that nine week of HSu-diet, which mimics at least in part Western diets [10,11,47], can lead to impaired hepatic glucose and lipid metabolism, typical features of T2DM, already present in this prediabetic model, even in the absence of obesity. This animal model of diet-induced prediabetes shows reduced glucose tolerance, postprandial hyperglycemia, hyperinsulinemia, reduced insulin sensitivity (resistance), and hypertriglyceridemia, together with impaired gluconeogenesis and lipogenesis ( Figure 8).…”
Section: Discussionmentioning
confidence: 99%
“…The dietary biomarker classification (i.e., recovery, concentration, replacement, or predictive biomarkers) would depend on the metabolite properties (29,67,73). Previous epidemiologic studies have identified metabolite profiles of predominantly data-driven (3,(74)(75)(76), or geography-defined dietary patterns (77,78). Some predefined dietary patterns have been explored for their effects on metabolite concentrations.…”
mentioning
confidence: 99%
“…Food metabolome, i.e., the sum of all metabolites that are derived from the digestion and biotransformation of food components [114], enables the use of a combination of biomarkers to assess exposure to dietary components [115], food groups [116], [117], or even dietary patterns with high specificity [118], [119]. More importantly, the largely unexploited food metabolome will also certainly lead to the discovery of novel biomarkers for dietary exposure and/or diet-disease relationships with a high level of detail and precision [114].…”
Section: Methodologies To Assess Energy Intake and Appetite-related Pmentioning
confidence: 99%